Pengembangan Media Belajar pada Operasi Hitung untuk Tingkat Sekolah Dasar - Nur Malasari; Arif Rahman Hakim (JKPM (Jurnal Kajian Pendidikan Matematika), 2017)
Development of Learning Media on Counting Operations for Elementary School Level. The purpose of this study is to develop learning media on the counting operations used in elementary school mathematics learning. This research was conducted on students in Madrasah Ibtidaiyah Assalam and SD Negeri 02 Kramat Jati. The research model used to develop this media is ADDIE (Analysis; Design; Development; Implementation; and Evaluation) model. In this research the product is tested to one media expert, three material experts, one development learning expert and one linguist. From the overall average value obtained from the experts validator in the form of percentage, namely: equal to 88,78% which means have very good criteria. Formative evaluation results from media experts with a value of 4.50 which means having very good criteria. Formative evaluation results from expert material I with a value of 4.20 which means has a very good criteria. Formative evaluation results from material experts II with a value of 4.75 which means has a very good criteria. Formative evaluation results from material experts III with a value of 4.75 which means has a very good criteria. Formative evaluation results from developmental learning experts with a value of 4.85 which means having very good criteria, and formative evaluation results from linguists get a value of 4.80 which means have very good criteria. Of all the formative evaluations the learning media on counting operations for the primary school level is categorized very well. In other words, the learning media developed in this study is considered feasible and excellent for use in mathematics learning.